38.3 ETHNIC DIFFERENCES IN INVOLUNTARY ADMISSION AND CLINICAL PRESENTATION AT FIRST HOSPITALIZATION AFTER PSYCHOSIS ONSET AMONG FIRST-GENERATION MIGRANT GROUPS IN CANADA. (9th April 2019) - Anderson, Kelly
Abstract: Background: Some ethnic minority groups have an increased risk of developing a psychotic disorder, and often face complex and aversive pathways to care. However, Canadian data on this trend is lacking, particularly regarding involuntary admission. It is also less clear whether some of these trends may be driven by ethnic differences in clinical presentation or its perception by service providers. Our objective was to assess whether there were differences across first-generation ethnic minority groups in hospitalization and involuntary admission after psychosis onset, and whether the groups differed in symptom and behavior profiles at first admission. Methods: Using population-based health administrative data, we constructed a retrospective cohort of first-onset cases of psychotic disorder in Ontario between 2009 and 2014. This cohort was linked to data from Immigration, Citizenship, and Refugee Canada for information on migrant status and country of origin. We followed the cohort for a two-year period after first diagnosis to ascertain the first psychiatric hospitalization event and compared the risk of having involuntary status for first-generation ethnic minority groups relative to a general population reference group. We also examined differences in symptoms, behaviour, and level of functioning across groups. Results: Of the 6204 psychiatric hospitalizations in our study cohort, 18.9% (n=1172) were attributed to first-generation migrants. Nearly all migrant groups had higher rates of both hospitalization and involuntary admission, and the findings were attenuated but remained statistically significant after adjustment for sociodemographic, clinical, and service-use factors. There was also evidence of effect modification by gender, with African males and Caribbean females having particularly high rates of involuntary admission. There was also evidence of differences across groups in clinical presentation at first hospitalization, with migrants from the Caribbean demonstrating the greatest differences in clinical presentation – in particular, Caribbean migrants were more likely to be perceived as demonstrating aggressive behaviour and posing a risk of harm to others. All migrant groups had a lower prevalence of alcohol and substance use at first admission. Conclusions: Our findings are consistent with the international literature showing increased rates of involuntary admission among some ethnic minority groups with first-episode psychosis. Our findings also suggest that some first-generation migrant groups may differ in clinical presentation at the first hospitalization after psychosis onset. It is unknown whether the observed differences are due to delayed help-seeking, the perception of service providers, or true differences in clinical presentation across ethnic minority groups. Interventions aimed at improving pathways to care could be targeted at these groups to reduce disparities in access to care for people with psychotic disorders.